Book Review: Florence Bonacina-Pugh (2024). Language Policy as Practice: Advancing the Empirical Turn in Language Policy Research - Ritonga, Apri Wardana; Bahruddin, Uril; Abdul Aziz (East European Journal of Psycholinguistics, 2025)
This review explores the theoretical, methodological, and empirical contributions of Language Policy as Practice, edited by Florence Bonacina-Pugh. The book represents a significant shift in the study of language policy from normative and macrostructural approaches toward empirical ones that foreground language practices in real social contexts. Across eleven diverse chapters, the contributors present ethnographic studies and in-depth interactional analyses of language policy as it unfolds in various domains, including classrooms, higher education institutions, transient communities, and households. The book’s central focus is on how language policies are not merely top-down directives but are interpreted, negotiated, and enacted situationally by local actors in their everyday lives. This review appreciates the "language policy as practice" approach advanced in the book while also addressing its conceptual and methodological challenges. By emphasizing a human-centered perspective, the book invites readers to envision a future of language policy that is more inclusive, equitable, and grounded in the lived experiences of its users.